Is outpatient cognitive remediation therapy feasible to use in randomized clinical trials for anorexia nervosa?. Issue 6 (29th April 2013) - Lock, James; Agras, W. Stewart; Fitzpatrick, Kathleen Kara; Bryson, Susan W.; Jo, Booil; Tchanturia, Kate
<x xml:space="preserve">Abstract</x> Objective There are limited data supporting specific treatments for adults with anorexia nervosa (AN). Randomized clinical trials (RCTs) for adults with AN are characterized by high attrition limiting the feasibility of conducting and interpreting existing studies. High dropout rates may be related to the inflexible and obsessional cognitive style of patients with AN. This study evaluated the feasibility of using cognitive remediation therapy (CRT) to reduce attrition in RCTs for AN. Method Forty‐six participants (mean age of 22.7 years and mean duration of AN of 6.4 years) were randomized to receive eight sessions of either CRT or cognitive behavioral therapy (CBT) over 2 months followed by 16 sessions of CBT for 4 months. Results During the 2‐month CRT vs. CBT treatment, rates of attrition were lower in CRT (13%) compared with that of CBT (33%). There were greater improvements in cognitive inefficiencies in the CRT compared with that of the CBT group at the end of 2 months. There were no differences in other outcomes. Discussion These results suggest that CRT is acceptable and feasible for use in RCTs for outpatient treatment of AN. CRT may reduce attrition in the short term. Adequately powered future studies are needed to examine CRT as an outpatient treatment for AN. © 2013 by Wiley Periodicals, Inc. (Int J Eat Disord 2013; 46:567–575)